E-money: opportunities for quick payments and risks of their use for illegal purposes - A. A. Koval; M. Yu. Kuzmenkov (Вестник Российского экономического университета имени Г. В. Плеханова)
E-money is widely used in cross-border commercial relations. It can increase the speed and cut cost of payments for business. At the same time e-money can be used for laundering funds gained by criminal ways and for terrorism financing. FATF member-states use provisions of the legislation about fighting criminal incomes’ legalization in respect to e-money issuers. These countries also underline that special risk for criminal incomes’ legalization can be caused by anonymous money and pre-paid cards. Therefore, many countries fix in their national laws measures that ensure realization of risk-oriented approach directed at minimizing risks of money laundering and terrorism financing. For example, the EU develops amendments to the directive aiming at elimination of risks dealing with use of e-money and pre-paid cards for legalizing criminal incomes. The authors propose measures aimed at improvement of legislation about fighting money laundering and terrorism financing to minimize respective risks in using e-money. At the same time the necessity to develop conditions for extending possibilities of remote identification was pointed out, as it was envisaged by the program ‘Digital Economics of the Russian Federation’.